Using the terrestrial laser scanner and simple methodologies for geometrically assessing complex masonry vaults. - Costa-Jover, Agustí; Lluis i Ginovart, Josep; Coll-Pla, Sergio; López Piquer, Mónica (Journal of Cultural Heritage, 2019)
Abstract In recent years, the development of massive data capture techniques, such as the Terrestrial Laser Scanner (TLS), has raised the possibility of developing new procedures for assessing architectural heritage. The 3D models that can be obtained through these techniques are a tool of great potential for both conservation purposes and historical and architectural studies. This paper proposes a simple, non-invasive methodology for assessing masonry vaults from the point clouds, making it possible to obtain relevant data on formal anomalies. The methodology was tested in the Gothic Tortosa Cathedral's vaults. This study found geometrical differences between vaults, a priori equal, which were related to the partially-known construction phases. The procedure can be applied easily to other vaulted constructions of any kind but is especially useful in dealing with the complex geometry of Gothic masonry vaults.